Impact of Wilms’ tumor 1 gene (WT1) mutation on outcome of allogeneic hematopoietic-cell transplantation for acute myeloid leukemia: a retrospective multicenter cohort study from the ALWP/EBMT registry - Nagler, Arnon; Esteve, Jordi; Galimard, Jacques-Emmanuel; Sanz, Jaime; Poire, Xavier; Collin, Matthew; Maertens, Johan; Huang, He; Itäla-Remes, Maija; Halahleh, Khalid; Pascual Cascon; Maria Jesús; et al. (Springer Science and Business Media LLC, 2026)
We compared transplantation outcomes of AML patients with WT1 mutation (mWT1), identified by next-generation sequencing, to those of patients with wild-type WT1 AML (wtWT1). 703 patients were included, 50 with mWT1 and 653 with wtWT1. Patients with mWT1 were younger (median age: 45.6 vs. 56.4 years, p < 0.001), with a higher proportion of females (66% vs. 47.6%, p = 0.01), higher frequency of mutations in FLT3-ITD (38.3% vs. 21.7%, p = 0.01) and CEBPA (15.8% vs. 5.7%, p = 0.03). Donors were matched siblings in 30.6%, unrelated in 45.6%, and haploidentical in 22.1%. A higher percentage of mWT1 vs. wtWT1 patients received in vivo T-cell depletion (66% vs. 51%, p = 0.03) and 58% vs. 47.1% received myeloablative conditioning. 49 patients with mWT1 were matched to 127 wtWT1 patients in matched-pairs analysis. Outcomes (mWT1 vs. wtWT1) were not significantly different: relapse (2 y: 28.8% vs. 30.4%, HR: 1.14, p = 0.64), NRM (2 y: 15.5% vs. 9.9%, HR: 1.41, p = 0.49), LFS (2 y: 55.7% vs. 59.6%, HR: 1.21, p = 0.39), OS (2 y: 65.4% vs. 73.3%, p = 0.66), and chronic GVHD (2 y:24.3% vs. 25.4%, p = 0.95). In conclusion, WT1 mutation did not influence transplantation outcomes of AML patients in CR1.